2018
DOI: 10.1186/s12917-018-1616-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Clostridioides (Clostridium) difficile in feces of calves of different age and determination of predominant Clostridioides difficile ribotype 033 relatedness and transmission between family dairy farms using multilocus variable-number tandem-repeat analysis

Abstract: BackgroundCommunity acquired Clostridioides (Clostridium) difficile infection (CA-CDI) is a significant health problem in human and veterinary medicine. Animals are often considered as potential reservoirs for CA-CDI. In Europe, family farming is the most predominant farming operation, with a complex interaction between animals and the community. Therefore, it is pertinent to evaluate transmission patterns of C. difficile on such prominent European farming model.Fecal samples from calves (n = 2442) were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
4
13
1
Order By: Relevance
“…As the piglets aged, the concentration, as well as the prevalence of C. difficile -positive piglets, gradually decreased and, at the same time, the microbial diversity increased. Similarly, a decrease in the shedding load of C. difficile with age could be observed in calves [31]. We also found that a decrease in the C. difficile level was inversely associated with microbial diversity indices in suckling piglets.…”
Section: Discussionsupporting
confidence: 70%
“…As the piglets aged, the concentration, as well as the prevalence of C. difficile -positive piglets, gradually decreased and, at the same time, the microbial diversity increased. Similarly, a decrease in the shedding load of C. difficile with age could be observed in calves [31]. We also found that a decrease in the C. difficile level was inversely associated with microbial diversity indices in suckling piglets.…”
Section: Discussionsupporting
confidence: 70%
“…There were no records on the transport of animals between the farms in the study. Intra-farm relatedness of RT033 C. difficile isolates was also observed in the study of Bandelj et al [ 37 ]. Clonal groups of ST 11 C. diffcile isolates from different states, countries and continents were also identified by core genome single nucleotide variant analysis suggesting possible zoonotic/anthroponic transmission [ 15 ].…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, faecal samples were collected from the barn of each herd and not from each calf. As a result, the main limitation of the study is the impossibility to analyse prevalence within the herd as well as the age as the recognised main risk factor [35]. Furthermore, we cannot exclude that recontamination from the farm environment might have occurred.…”
Section: Discussionmentioning
confidence: 97%